2005
DOI: 10.1002/cne.20793
|View full text |Cite
|
Sign up to set email alerts
|

DNA topoisomerase I in the mouse central nervous system: Age and sex dependence

Abstract: Topoisomerase I (topo I) is a nuclear enzyme responsible for the topological state of DNA and therefore participates in most DNA transactions, particularly in transcription. Topo I, a ubiquitous enzyme, was identified and characterized in various cell types and tissues; however, the characterization of topo I in the intact central nervous system was not performed. Here we investigated, for the first time, the activity, level, and distribution pattern of topo I in the various selected brain regions in the mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…With regard to TOP1, in addition to obtaining identical results using two independently generated monoclonal antibodies, our observation that TOP1 is localized to the nucleolus and nucleoplasm is consistent with other studies on the distribution of this enzyme within the nucleolus [23], and nucleus, including observations of GFP-tagged TOP1 in living human cells [24,25]. It should be noted that in one study [34], cytoplasmic TOP1 staining was observed in the mouse Purkinje neurons. However, in another study [35] TOP1 staining was observed in the nucleolus of postnatal rat Purkinje neurons, consistent with our findings.…”
Section: The Mrn-complex and Topoisomerase I Are Also Concentrated Insupporting
confidence: 89%
See 1 more Smart Citation
“…With regard to TOP1, in addition to obtaining identical results using two independently generated monoclonal antibodies, our observation that TOP1 is localized to the nucleolus and nucleoplasm is consistent with other studies on the distribution of this enzyme within the nucleolus [23], and nucleus, including observations of GFP-tagged TOP1 in living human cells [24,25]. It should be noted that in one study [34], cytoplasmic TOP1 staining was observed in the mouse Purkinje neurons. However, in another study [35] TOP1 staining was observed in the nucleolus of postnatal rat Purkinje neurons, consistent with our findings.…”
Section: The Mrn-complex and Topoisomerase I Are Also Concentrated Insupporting
confidence: 89%
“…However, in another study [35] TOP1 staining was observed in the nucleolus of postnatal rat Purkinje neurons, consistent with our findings. Whether the discrepant observations [34] represent a species difference, a methodological difference, or non-specific staining remains to be determined.…”
Section: The Mrn-complex and Topoisomerase I Are Also Concentrated Inmentioning
confidence: 99%
“…Mouse brain shows substantial levels of topo I activity varying among different brain regions (Plaschkes et al, 2005). Immunohistochemistry shows that the highest topo I levels are observed in inhibitory neurons.…”
Section: Jsmentioning
confidence: 99%
“…Eukaryotic type I topoisomerase (topo IB) plays important roles in DNA replication, RNA transcription, DNA recombination, chromosome condensation, and the maintenance of genomic stability (Champoux, 2001;Wang, 2002). Immunohistochemical analysis in selected mouse brain regions reveals that a significant level of topo I activity is present in the brain, and the level of topo I activity varies among different brain regions (Plaschkes et al, 2005). The cerebellum, visual cortex, and the striatum exhibit higher topo I activity than the hippocampus and hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation